If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 + -2x = 19 Reorder the terms: 7 + 6x + -2x = 19 Combine like terms: 6x + -2x = 4x 7 + 4x = 19 Solving 7 + 4x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 19 + -7 4x = 19 + -7 Combine like terms: 19 + -7 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 5x+7(x-1)=-3 | | 2y-6=2x | | 5a+10=3a+10 | | x+(x*0.07)=35.19 | | 14(t-6)+4t=6(3t+5)-8 | | (6x-6)-(13x+8)= | | 3x-5(x-3)=16-4x | | x+(x*0.07)=28.25 | | -13x=234 | | -(4y+4)-(-3y-8)=-2 | | 1/4+3/8x=3/4 | | 3.5+0.75x=17.00 | | 10x+5/2y=20 | | 2x-1-.5-6x-x= | | x+(x*0.07)=131.8 | | 8/3x+1/3x=5x+65/3+7/3x | | -2(3s-1)-2=-2(5s+6)-2 | | x+8=38 | | -20x+5(2-3x)=40-6x | | 8+4(x-3)=9-5(x-4) | | x+(x*0.07)=148.35 | | 45-(2c+4)=4(c+5)+c | | 4/7+6/11 | | 6y=15 | | X+x^2+2x^2-3x= | | x+(x*0.07)=81.2 | | 6-94x=7x-9x+2 | | 15r+14=90 | | x^3-3x^2-3x+4=0 | | -k-2n-5+8n=65 | | -x+3=3x-6 | | x+(x*0.07)=63.55 |